Handbook of electrogastrography - Koch, Kenneth L. (Oxford University Press, 2004)
The Handbook of Electrogastrography is the first textbook dedicated to reviewing the physiology of gastric myelectrical activity and the measurement of this electrical activity with electrodes placed on the abdominal surface - the electrogastrogram. The Handbook is divided into three major sections. The first section (Chapters 1-3) focuses on the history of electrogastrography, electrical activity of the interstitial cells of Cajal, the cells from which gastric electrical rhythmicity emanates. The cellular level of gastric electrical rhythmicity provides an understanding of the physiological basis of the electrogastrogram signal...